Enhanced SOFC Cathode Performance Through Surface Modification of NdBa0.5Sr0.5Co2O5+δ Nanoparticles - Adi Subardi (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2022)
The cathode materials fabrication with outstanding performance and stability at intermediate temperatures of 600–800℃ is required for the prospective mass production of solid oxide fuel cells (SOFCs). Infiltration is a potential method because it has proven successful in fabrication and cell performance enhancement. This study mainly focuses on the electrical conductivity and long-term reliability of cathode symmetric cells NdBa0.5Sr0.5Co2O5+δ (NBSC) fabricated by traditional solid-state reaction techniques. The electrical conductivity value of the cathode is in the range of 174–278 S.cm-1. Impedance analysis showed that the infiltration of 0.5M SDC on the NBSC cathode surface dramatically reduced the polarization resistance (Rp) between layers (cathode-electrolyte) from 3.32 Ω.cm2 to 1.82 Ω.cm2 at 600℃ or decreased by 45 % compared to NBSC cathode without 0.5M SDC infiltration. The enhanced stability of NBSC cathode specimens with 0.5M SDC infiltration (NBSC+0.5 M SDC) under SOFC operating conditions proves that samples with infiltration extend their lifetime. Compared to the NBSC cathode, the NBSC+0.5 M SDC cathode has better long-term stability with a lower RP value of 2.35 Ω.cm2. In the OPP range of 0.214-0.0027 atm at 800℃, the relatively tiny Rp value of the symmetrical cell is between 0.030 Ω.cm2 and 0.039 Ω.cm2, below the 0.15 Ω.cm2 suitable performance limit for solid oxide fuel cells.